From TPPA to CPTPP: potential impact on Malaysia's finance, banking and trade - Rashid, Salim; Zainal Abidin, Irwan Shah (Universiti Utara Malaysia Press, 2019)
The Trans-Pacific Partnership Agreement (TPPA) is an economic partnership pact negotiated by 12 countries in three continents, namely Australia, Brunei, Canada, Chile, Japan, Malaysia, Mexico, New Zealand, Peru, Singapore, United States and Vietnam. The TPPA has evolved into the Comprehensive and Progressive Agreement for Trans Pacific Partnership (CPTPP), when the United States pulled out from the multilateral free trade deal in 2018. Malaysia began negotiations on the TPPA in August 2010, and participated as a full negotiating member from October 2010 onwards. The TPPA itself was based on the United States-Korea Free Trade Agreement (KORUS), which was completed in 2011. This agreement provided a benchmark to decide and evaluate on several issues in the CPTPP. The overall intent of the CPTPP is a simple one: it is to extend non-discriminatory practices to all CPTPP members. This does not mean that regulations and restrictions will not exist— that such regulations will apply equally to Malaysian and non-Malaysian CPTPP members. Contentious issues in the CPTPP will be analyse and discuss in this book. Is the Malaysian economy ready for the CPTPP rules especially in the financial and capital markets? To what extent that Bank Negara’s ability to retain their power to intervene when either the balance of payments or the currency is felt to be under threat with CPTPP? What are the impacts of CPTPP to the real economic side of the Malaysian economy? Will national rights are being relinquished under CPTPP? How about the concern over investor-state dispute settlement (ISDS)? This book will address these issues in an objective and rational manner.